Pictorial as readable: ekphrasis in a literary work and reader’s perception - Lubov I. Semerenko; Oleksandr O. Pliushchai (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The interaction of arts which poets, writers, artists, scholars and philosophers have always paid considerable attention, has gained popularity recently and it has been given serious consideration in art history, literary and cultural studies, and aesthetics. Some researchers explain a growing interest in the phenomenon of increasing significance of visuality in modern culture. The aim of the article is to clarify the status quo in the study of ekphrasis in literary and cultural studies. To achieve the aim pursued, the following research methods have been used: cultural-aesthetic, comparative and hermeneutic. The paper focuses on the concept of ekphrasis and its use in literary works and studies the current trends in the study of ekphrasis, regarding its definition, typology, functions, ekphrastic genre invariants, and reader’s perception of ekphrasis. Some exemplary instances of ekphrasis description in English ekphrastic poetry and emotive prose have been considered, and the verbal means of ekphrasis generation have been analysed. The analysis of the most popular works of domestic and foreign scholars such as: N.S. Bochkareva, L. Geller, N.N. Yefimova, A.Yu. Krivoruchko, V. Cunningham, J. Hollander, L. Spitzer and many others, has allowed to make the conclusion that most scholars use the definition of ekphrasis as a “poetic description of a pictorial or sculptural work of art” suggested by Leo Spitzer, although, the definition of ekphrasis as a “verbal representation of visual representation” of James Hefferman, which is a broader concept is also popular. Different classifications of ekphrasis have been suggested by the researchers. N. Braginskaya, for instance, distinguishes the dialogical and monological ekphrasis on the basis of the internal structure of the text, the main difference being the manner of presenting information to the reader. The typology of ekphrasis and its main functions are mainly given on the basis of creative works of a particular writer or poet and many researchers pay attention to sense general features of ekphrasis as the process which combines iconic and sign images in verbal discourse. Ekphrasis, being the representation of other arts in literature, expands considerably the narrative space. The origin of ekphrasis goes back to the ancient times where it is seen as a rhetorical device. In classical rhetoric, ekphrasis could refer virtually to any extended description of art objects. Ekphrasis, an ancient rhetorical term, has been now revived in academic circles, in the studies of art and literature. After languishing in obscurity until 1967, when Murray Krieger published a notable essay on it, ekphrasis is commanding major attention, “ploughing the inexhaustibly fertile ground where literature meets visual arts”. There are various approaches to the study of the ekphrastic tradition, and the historical approach being one of them, can be seen in many works. Ekphrasi in modern research is a multifaceted and polyfunctional phenomenon. The typology of ekphrasis and its main functions are mainly given on the basis of the particular poet`s or writer`s creative works, paying attention to some general features of ekphrasis which combines iconic and sign images in verbal discourse. The phenomenon of ekphrasis merits further consideration, especially, due to the availability of Liliane Louvel’s The Pictorial Third: An Essay into Intermedial Criticism, which provides the author’s innovative approach to the understanding of the relationships between the literary text and image.